The Importance of Grammar in Communication - Habiburrahman, Muhammad; Siregar, Aulia Sabrina; Tanjung, Nur Rahmaida; Lubis, Yani (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Effective communication heavily relies on the correct use of grammar. This study explores the pivotal role of grammar in facilitating clear, accurate, and credible information exchange, as well as its impact on the communicator's professionalism. Employing a library research methodology, this review analyses existing academic materials to identify and synthesize effective strategies for improving grammar mastery in English communication. Findings indicate that explicit grammar instruction, contextualized and task-based learning, and the utilization of digital technology are highly effective methods. Furthermore, learner motivation and consistent teacher support are identified as crucial enabling factors. While acknowledging various pedagogical approaches, this research concludes that an integrated or